Templated Synthesis of Diamond Nanopillar Arrays Using Porous Anodic Aluminium Oxide (AAO) Membranes - Chenghao Zhang; Zhichao Liu; Chun Li; Jian Cao; Josephus G. Buijnsters (Nanomaterials, 2023)
Diamond nanostructures are mostly produced from bulk diamond (single- or polycrystalline) by using time-consuming and/or costly subtractive manufacturing methods. In this study, we report the bottom-up synthesis of ordered diamond nanopillar arrays by using porous anodic aluminium oxide (AAO). Commercial ultrathin AAO membranes were adopted as the growth template in a straightforward, three-step fabrication process involving chemical vapor deposition (CVD) and the transfer and removal of the alumina foils. Two types of AAO membranes with distinct nominal pore size were employed and transferred onto the nucleation side of CVD diamond sheets. Subsequently, diamond nanopillars were grown directly on these sheets. After removal of the AAO template by chemical etching, ordered arrays of submicron and nanoscale diamond pillars with ~325 nm and ~85 nm diameters were successfully released.